Dry season woody fodder productivity in savannas - BRISSO, Nassirou; HOUINATO, MARCEL ROMUALD BENJAMIN; ADANDEDJAN, COCOU CLAUDE; SINSIN, AUGUSTIN BRICE (My University, 2007)
The objective of this study was to assess the woody fodder production based on local herdsmen pruning pratices. The method consisted firsty in using a questionnaire to evaluate species utilised followed by sampling and estimation of yield of trees utilised. Browsing on woody fodder in the protected forest of Wari-Maro in Benin concerns mainly three species : Khaya senegalensis, Afzelia africana and Pterocarpus erinaceus which are exploited by cattle keepers. Fooder tree production varied significantly according to the species but was less in the dry season. There was a relation between diameter and biomas produced by species. Pruning was the main method used to utilise trees.
Keywords: Tree fodder; browse; yield; cattle